Solidification of spherulitic iron castings at continuous cyclic casting - E. I. Marukovich; V. S. Mazko; V. I. Stetsenko (Литьë и металлургия)
The peculiarities of spherulitic iron castings formation during continuous cyclic casting are investigated.